Driven by temper: Personality, mental health, and road rage among commercial drivers - Tamuno-opubo, Addah Temple; Lawal, Damilola B.; Akadri, Toluwalase; Edisemi, Ali Prince; Nwankwo, Chinemerem David (Journal of Indonesian Psychological Science (JIPS), 2025)
Road rage has become an increasing concern in densely populated urban areas, posing significant risks to road safety and public health. This study examined the influence of personality traits and mental health status on road rage among commercial drivers in Lagos Metropolis, Nigeria. A descriptive survey design was adopted, involving a sample of commercial drivers selected through a multistage sampling technique. Data were collected using standardized instruments that measured driving anger, personality characteristics, and mental health status. The analysis revealed meaningful associations between personality dimensions, mental health conditions, and the propensity for road rage. Findings suggest that drivers exhibiting certain personality patterns and compromised mental health are more susceptible to aggressive driving behaviours. These results underscore the importance of integrating psychological and behavioural considerations into road safety interventions. Promoting emotional regulation and providing accessible mental health support could be crucial strategies for reducing road rage, particularly among commercial drivers operating in high-stress urban environments such as Lagos.